Dinamika Populasi dan Produktivitas Sapi Madura di Wilayah Konservasi Pulau Sapudi - Farahdilla Kutsiyah (Universitas Sebelas Maret (UNS), 2017)
The study was conducted to determine population dynamic, productivity, and output of Madura cattle in a conservation area of Sapudi Island. The number of respondents was 108 farmers and 361 heads of madura cattle taken from six (6 villages). The sampling technique used accidental sampling method and data was counted by descriptive analysis. The results showed that S/C 1,68±0,87 times, calving interval 14,56±2,15 months, and the efficiency reproductive value (ER) was 93,21%. natural increase (NI) value of Madura cattle in Sapudi Island in 2014 was 27.96%. Net replacement rate (NRR) value of sire and dam of cattle were 96,18 % dan 126,41% respectively. Output estimation was 30,75% population dynamic of maduracattle in 2015 to 2019 has estimated that will be decreased 566 heads or -0.09% per year. It was concluded that the population in Sapudi Island has been dumped and the need for replacement bulls is not fulfilled. Therefore action should be taken to reduce the expenditure of livestock, especially bulls and provide the supporting infrastructure which supports it, one of the most required right now is the availability of feed and water infrastructure.